Performance Enhancement of the Natural Draft Porous Surface Domestic Cooking Burner using Secondary Aeration - Pradhan, Premananda; Chandra Mishra, Purna (International Journal of Engineering and Technology, 2018)
This paper presents the effect of secondary aeration on the performance of a novel natural draft porous surface burner for domestic cookstove applications. TheÂ burner isÂ designed and developed in contrast to the principle adapted so far in bi-layer porous burners. Liquefied Petroleum Gas (LPG) is the only test fuel used in the experiment. The experimental results revealed that the thermal efficiency ofÂ the burnerÂ is 71.78% which is about 7% more efficient as compared to the best conventionalÂ free flame burnerÂ operating within the range of 0.55 to 2kW. CO and NOx emissions are significantly lower than the conventional free flame LPG burners. Provision for mixing of secondary air with preheated primary air-fuel mixture in the combustion chamber is made through the tubes attached to the body of the burner through natural drafting. Further reduction in CO values to 32ppm with an improvement in maximum thermal efficiency to 73.22% is also observed with secondary aeration by natural draftÂ Â